Brachiopoda 2025: A review and update - Sandra J. Carlson; Paul C. Fitzgerald; Glenn S. Jaecks; Judith A. Sclafani (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Relationships among peri-traumatic circulating endocannabinoids and long-term, negative outcomes following traumatic injury - Emily A. Albertina; Carissa W. Tomas; Timothy J. Geier; Sydney C. Timmer-Murillo; Isela G. Pina; Kelley Jazinski-Chambers; Garrett Sauber; Jacklynn M. Fitzgerald; Christine L. Larson; Terri A. deRoon-Cassini; Cecilia J. Hillard (Psychopharmacology, 2026)
Rationale Traumatically injured individuals can develop chronic negative psychological sequelae. Improved understanding of contributing, peri-traumatic risk factors is essential to reduce the risk of these consequences. Previous studies have found that peri-traumatic, circulating endocannabinoid concentrations are positively associated with development of post-traumatic stress disorder (PTSD), chronic pain and depression months later, particularly in members of racial/ethnic groups that have been historically marginalized. Objectives This replication study examined relationships among peri-trauma serum endocannabinoid concentrations and long-term consequences in a cohort comprised primarily of individuals from marginalized racial and ethnic groups. Methods Participants ( n = 100; 81% from marginalized racial and ethnic groups) were traumatically injured adults presenting to the ED of an urban tertiary care hospital. Endocannabinoids N -arachidonoylethanolamine (AEA) and 2-arachidonoylglycerol (2-AG) were measured in serum collected within days (peri-trauma) and 6–10 months following injury (follow-up). Assessments, including PTSD, depression, pain and quality of life were completed. Statistical approaches, including multivariate, hierarchical regressions, were used to determine associations among serum endocannabinoid concentrations and long-term outcomes. Results Although it did not survive correction for multiple comparisons, peri-trauma serum 2-AG concentrations. Peri-trauma serum 2-AG concentrations were also positively associated with PTSD, pain severity, and functional engagement scores at follow-up. There were no significant associations between circulating 2-AG or AEA and depression. Conclusions These findings generally replicate earlier studies demonstrating that serum 2-AG concentrations are biomarkers of risk for PTSD and pain and uncover an additional association with poor functional quality of life. Further studies are needed to determine the underlying mechanisms of these relationships.

Characterization and insecticidal effects of the essential oil and nanoemulsion of Pogostemon cablin on populations of Sitophilus zeamais - Álvaro M.O. Santos; Ana Paula A. Araújo; Péricles B. Alves; Arie Fitzgerald Blank; Eliseu J.G. Pereira; Raul N.C. Guedes; Rogéria S. Nunes; Marcelo C. Picanço; Virginia E. Masiulionis; Leandro Bacci (Crop Protection, 2026)

Facial skin aging: an integrative analysis of genetics, epigenetics, and lifestyle factors - Rezvan Noroozi; Aleksandra Pisarek-Pacek; Bożena Wysocka; Kamila Migacz-Gruszka; Paulina Pruszkowska-Przybylska; Magdalena Kobus; Dagmara Lisman; Julia Zacharczuk; Joanna Rudnicka; Aleksandra Iljin; Kathryn C. Fitzgerald; Małgorzata Michalczyk; et al. (GeroScience, 2025)
Facial wrinkling is a prominent sign of aging, yet individuals exhibit unique trajectories of biological aging, contributing to the variability in facial appearance. Here, we present a pioneering study exploring the association between lifestyle choices, DNA methylation, and SNP genotypes with a range of facial skin aging phenotypes. The study demonstrated that age-related facial skin phenotypes are influenced by multiple environmental stressors. Epigenome-wide association analyses identified differentially methylated cytosines mapped to 151 loci , including novel genes associated with facial wrinkles, such as EDAR (cg02925966, p = 4.96 × 10 −8 ) and NRG1 (cg26267340, p = 4.64 × 10 −8 ), both involved in wound healing. Sensitivity analysis, conditioning on the top meQTLs, showed minor attenuation, suggesting an association independent of genetic variants. Accelerated epigenetic aging, measured in the blood of over 700 Polish individuals, was found to correlate with facial wrinkle area, photoaging, telangiectasias, and perceived facial age, with the GrimAge and FitAge clocks showing the most robust associations. Genome-wide SNP analysis identified rs73943403 (RP11-78F17.1, p = 3.72 × 10 −8 ) associated with wrinkle area and rs113125564 ( ZC3H4 , p = 1.23 × 10 −8 ) associated with perceived facial age, potentially implicating stress response and adiposity in skin aging. Finally, the study revealed the additive value of methylation and SNP data for predicting two continuous skin phenotypes, with 59.0% of the variation explained in facial wrinkle area and 26.2% in perceived facial age. The findings underscore the relevance of genetic and epigenetic factors, revealing novel candidate genes and molecular pathways involved in skin aging. These insights hold substantial translational value for dermatology, the cosmetics industry, and anti-aging strategies.

Empowerment of parents of infants with congenital heart disease after rapid genome sequencing - Rita M. Cheney; Gabrielle C. Geddes; Sara M. Fitzgerald-Butt (Journal of Community Genetics, 2025)
Background Despite rapid genome sequencing (rGS) being utilized as a first-tier genetic test for infants with congenital heart disease (CHD), little is known about its impact on parental empowerment. Methods To address this gap, parents of infants with CHD (≤ 1 year old at the time of inpatient rGS) were asked to participate in an online survey, which measured empowerment using an adapted version of the Genomic Empowerment Scale (GEmS). The scale consists of four subscales that measure emotional management, meaning making, seeking information and support, and implications and planning surrounding a child’s diagnosis. Subscale scores were standardized for comparison and coded as above (+) or below (-) the mean. Based on the standardized score pattern (+/-) in each subscale, an empowerment profile was assigned to each participant. Empowerment profiles were analyzed for trends based on CHD type (left ventricular outflow tract obstruction (LVOTO) vs. non-LVOTO), genetic test result type, and number of genetics visits. Results The most common empowerment profile was the ‘Engaged but Worried Planner’ (15/37 = 41%). This empowerment profile was more common in parents of infants with non-LVOTO CHD (73.3%) than those with LVOTO CHD (26.7%). Conversely, there was little difference in empowerment profile type between rGS result type. Parents whose child had ≤ 3 genetics visits displayed the ‘Engaged but Worried’ profile most often, whereas those with ≥ 4 visits had more even distributions between profiles. Conclusion Understanding empowerment profiles in this population may help guide practitioners to empower parent decision-making, emotional management, and planning for the future of their child.

Size matters: a new view of the relationship between shape and size for molten volcanic ballistics - A. Sork; B. Kennedy; L. Watson; J. Taddeucci; R. Fitzgerald; M. Sellier; C. Biensan; D. Andronico; P. Scarlato; E. Del Bello; T. Ricci (Bulletin of Volcanology, 2025)
Volcanic ballistic projectiles (VBPs) are a common hazard near volcanic vents and often threaten volcano tourists, especially at accessible volcanoes with Strombolian eruption style. Current ballistic hazard models used to estimate potential VBP impact zones often assume round and solid (fixed shape) projectiles, though the validity of these assumptions remains uncertain. In this study, we use high-speed video observations to examine the shape and size distribution of molten VBPs, termed “bombs” from Strombolian eruptions at Stromboli (in 2014 and 2017) and Etna (in 2014) volcanoes (Italy). We provide a framework for describing in-flight bomb shapes, defining three shape classes (rounded, elongate, and bilobate) and subclass end members. The ratio of rounded to total VBPs decreases with size; most bombs (71% of the total catalogued) are smaller than 0.16 m and tend to be rounded (53% at all sizes and 62% for < 0.16 m); however, 80% of the bombs larger than 0.32 m tend to be elongate or bilobate. This trend is generally consistent across Strombolian eruptions in both this study and previous studies. However, video datasets of bomb-bearing eruptions at Batu Tara (Indonesia, 2014, Strombolian to Vulcanian) and Cumbre Vieja (Canary Islands, 2021, strong Strombolian and high fire-fountaining) show fewer elongate and bilobate bombs, especially at larger sizes. This size-shape relationship presented here has not been previously accounted for in ballistic models but has the potential to provide a size-based drag coefficient within ballistic models, leading to more accurate modelling results.

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Interannual variation in survival of wild Atlantic salmon smolts through a dynamic estuarine habitat - J. Barry; C. Fitzgerald; J. O. Callaghan; R. Kennedy; R. Rosell; W. Roche (Fisheries Management and Ecology, 2024)
Migration timing is critical for diadromous fish, especially for survival. Migration through fresh water and estuarine transitional waterbodies may be an important early life survival bottleneck through potential exposure to anthropogenic pressures and predators. Monitoring smolt movement and survival through riverine and estuarine habitats is important for identifying causes of smolt mortality and the potential for directing focused, mitigating management actions. Acoustic telemetry was used to track 186 Atlantic salmon smolts during migration from the river Boyne to the Irish Sea on the east coast of Ireland during 2019–2021. Migration success from release to sea entry that ranged from 47% to 81% was linked to biotic (predation) and abiotic effects (water flow and water temperature). Predation was associated with interannual variation in smolt survival, with 5.4% of smolts consumed by marine mammals and 26.3% lost to unknown fates. Our findings contribute to the understanding of predation on smolts and also how water temperature, flow and tidal phase can influence this critical life stage of Atlantic Salmon, a species in decline across its range.

Delivering Medically Tailored Groceries to Adolescents and Young Adults Living with HIV - K. Smith; I. Assefa; C. Guss; J. Addison; E. Woods; S. Fitzgerald (Journal of the Academy of Nutrition and Dietetics, 2024)

Twenty years of volcano data at GeoNet—collection, custodianship, and evolution of open data on New Zealand’s volcanoes - Jonathan B. Hanson; Steven Sherburn; Yannik Behr; Karen M. Britten; Ery C. Hughes; Paul A. Jarvis; Oliver D. Lamb; Agnes Mazot; Rebecca H. Fitzgerald; Bradley J. Scott; Nico Fournier (Bulletin of Volcanology, 2024)
The GeoNet programme at GNS Science has monitored and managed data for volcanoes, earthquakes, landslides, and tsunami in Aotearoa New Zealand since 2001. Volcano monitoring data are collected from seismometers, acoustic sensors, GNSS receivers, webcams, remote gas monitoring sensors, and a range of environmental sensors, as well as manually during visits to volcanoes. The primary user of volcano data is the internal cross-specialised Volcano Monitoring Group (VMG), which fulfils the role of the national volcano observatory. GeoNet concentrates on automatic data collection and analysis, while supporting members of the VMG with manual data collection and interpretation. The application of open-data principles to both data and metadata has always been a core aspect of GeoNet; responses have been overwhelmingly positive, despite concerns regarding some high value, manually collected datasets. The website www.geonet.org.nz represents the primary data access portal. Data analysis and delivery applications are organised by data type rather than hazard, with no volcano-specific data applications. Most datasets have web-based and API delivery application options; both provide standard data formats from a cloud-based archive. One of the challenges for volcano data collection and management has been shifting from a reliance on manually collected data to automatic collection. Additionally, awareness of important questions related to Indigenous Māori data governance is increasing, although the associated impact is not yet understood. Overall, the current centralised, cooperative volcano monitoring and data collection and management system, which benefits from improved efficiency, interoperability, and data quality, has proved effective in Aotearoa New Zealand. Ongoing work aims to ensure optimal data collection and management for volcano monitoring and downstream activities.

The impact of heart valve and partial heart transplant models on the development of banking methods for tissues and organs: A concise review - Andrew D. Vogel; Rebecca Suk; Christa Haran; Patrick G. Dickinson; Kristi L. Helke; Marc Hassid; David C. Fitzgerald; Joseph W. Turek; Kelvin G.M. Brockbank; Taufiek Konrad Rajab (Cryobiology, 2024)

Digital strategies for nitrogen management in grain production systems: lessons from multi-method assessment using on-farm experimentation - A. F. Colaço; B. M. Whelan; R. G. V. Bramley; J. Richetti; M. Fajardo; A. C. McCarthy; E. M. Perry; A. Bender; S. Leo; G. J. Fitzgerald; R. A. Lawes (Precision Agriculture, 2024)
During the past few decades, a range of digital strategies for Nitrogen (N) management using various types of input data and recommendation frameworks have been developed. Despite much research, the benefits accrued from such technology have been equivocal. In this work, thirteen methods for mid-season N recommendations in cereal production systems were evaluated simultaneously, ranging from simple mass balance through to non-mechanistic approaches based on machine learning. To achieve this, an extensive field research program was implemented, comprising twenty-one N strip trials implemented in wheat and barley fields across Australia over four cropping seasons. A moving window regression approach was used to generate crop response functions to applied N and calculate economically optimal N rates along the length of the strips. The N recommendations made using various methods were assessed based on the error against the optimal rate and expected profitability. The root mean squared error of the recommendations ranged from 15 to 57 kg/ha. The best performing method was a data-driven empirical strategy in which a multivariate input to characterise field and season conditions was abundantly available and used to predict optimal N rates using machine learning. This was the only approach with potential to substantially outperform the existing farmer management, reducing the recommendation error from 42 to 15 kg/ha and improving profitability by up to A$47/ha. Despite being reliant on extensive historical databases, such a framework shows a promising pathway to drive production systems closer towards season- and site-specific economically optimum recommendations. Automated on-farm experimentation is a key enabler for building the necessary crop response databases to run empirical data-driven decision tools.

Analysis of multiple biomarkers revealed the size matters of Cu particles for barley response under foliar exposure - Izabela Jośko; Magdalena Kusiak; Magdalena Sozoniuk; Mikołaj Feculak; Kevin C.-W. Wu; Melissa Fitzgerald; Mohamed Salem Alyafei; Mohamed Salah Sheteiwy (Science of The Total Environment, 2024)

P24-09: Outcome of the re-assessment of Bisphenol A (BPA) safety of use in Food Contact Materials (FCMs) - Z. Al Harraq; C. Croera; J. M. Barat Baviera; C. Bolognesi; A. Chesson; P.S. Cocconcelli; R. Crebelli; D.M. Gott; K. Grob; C. Lambré; E. Lampi; M. Mengelers; et al. (Toxicology Letters, 2023)

Quality of reporting animal studies - Monika Batke; Emanuela Corsini; Rex Fitzgerald; Eugenio Scanziani; Henri Schroeder; Inger-Lise Steffensen; Beate C. Ulbrich; Henk van Loveren; Dina Waalkens-Berendsen; Detlef Woelfle; Ursula Gundert-Remy (Archives of Toxicology, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Integrase Inhibitors are Associated with Neuropsychiatric Symptoms in Women with HIV - Leah H. Rubin; Jane A. O’Halloran; Dionna W. Williams; Yuliang Li; Kathryn C. Fitzgerald; Raha Dastgheyb; Alexandra L. Damron; Pauline M. Maki; Amanda B. Spence; Anjali Sharma; Deborah R. Gustafson; Joel Milam; et al. (Journal of Neuroimmune Pharmacology, 2023)

Heatwaves and mortality in Queensland 2010–2019: implications for a homogenous state-wide approach - Richard C. Franklin; Hannah M. Mason; Jemma C. King; Amy E. Peden; John Nairn; Lauren Miller; Kerrianne Watt; Gerard FitzGerald (International Journal of Biometeorology, 2023)
Heatwaves are a significant cause of adverse health outcomes and mortality in Australia, worsening with climate change. In Queensland, the northeastern-most state, little is known about the impact of heatwaves outside of the capital city of Brisbane. This study aims to explore the impact of heatwaves on mortality across various demographic and environmental conditions within Queensland from 2010 to 2019. The Excess Heat Factor was used to indicate heatwave periods at the Statistical Area 2 (SA2) level. Registered deaths data from the Australian Bureau of Statistics and heatwave data from the Bureau of Meteorology were matched using a case-crossover approach. Relative risk and 95% confidence intervals were calculated across years, regions, age, sex, rurality, socioeconomic status, and cause of death. Heatwaves were associated with a 5% increase in all-cause mortality compared to deaths on non-heatwave days, with variability across the state. The risk of death on a heatwave day versus a non-heatwave day varied by heatwave severity. Individuals living in urban centers, the elderly, and those living in regions of lower socioeconomic status were most impacted by heatwave mortality. The relative risk of dying from neoplasms, nervous system conditions, respiratory conditions, and mental and behavioral conditions increased during heatwaves. As heatwaves increase in Queensland due to climate change, understanding the impact of heatwaves on mortality across Queensland is important to tailor public health messages. There is considerable variability across communities, demographic groups, and medical conditions, and as such messages need to be tailored to risk.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A Socio-ecological Imperative for Broadening Participation in Coastal and Estuarine Research and Management - L.A. Harris; T. Grayson; H.A. Neckles; C.T. Emrich; K.A. Lewis; K.W. Grimes; S. Williamson; C. Garza; C.R. Whitcraft; J. Beseres Pollack; D.M. Talley; B. Fertig; et al. (Estuaries and Coasts, 2022)
For most of the scientific disciplines associated with coastal and estuarine research, workforce representation does not match the demographics of communities we serve, especially for Black, Hispanic or Latino, and Indigenous peoples. This essay provides an overview of this inequity and identifies how a scientific society can catalyze representational, structural, and interactional diversity to achieve greater inclusion. Needed changes go beyond representational diversity and require an intentional commitment to build capacity through inclusivity and community engagement by supporting anti-racist policies and actions. We want to realize a sense of belonging on the part of scientists in society at large and enable research pursuits through a lens of social justice in service of coastal communities. Minimally, this framework offers an avenue for increased recruitment of individuals from more diverse racial and ethnic identities. More broadly, the mechanisms described here aim to create a culture in scientific societies in which social justice, driven by anti-racist actions, produces systemic change in how members of scientific societies approach, discuss, and address issues of inequity. We have written this essay for members of the coastal and marine science community who are interested in change. We aim to call in new voices, allies, and champions to this work.

Identification and molecular mapping of Rps14, a gene conferring broad-spectrum resistance to Phytophthora sojae in soybean - Liyang Chen; Weidong Wang; Jieqing Ping; Joshua C. Fitzgerald; Guohong Cai; Chancelor B. Clark; Rajat Aggarwal; Jianxin Ma (Theoretical and Applied Genetics, 2021)

Using expert knowledge to support Endangered Species Act decision‐making for data‐deficient species - Daniel B. Fitzgerald; David R. Smith; David C. Culver; Daniel Feller; Daniel W. Fong; Jeff Hajenga; Matthew L. Niemiller; Daniel C. Nolfi; Wil D. Orndorff; Barbara Douglas; Kelly O. Maloney; John A. Young (Conservation Biology, 2021)
Many questions relevant to conservation decision‐making are characterized by extreme uncertainty due to lack of empirical data and complexity of the underlying ecologic processes, leading to a rapid increase in the use of structured protocols to elicit expert knowledge. Published ecologic applications often employ a modified Delphi method, where experts provide judgments anonymously and mathematical aggregation techniques are used to combine judgments. The Sheffield elicitation framework (SHELF) differs in its behavioral approach to synthesizing individual judgments into a fully specified probability distribution for an unknown quantity. We used the SHELF protocol remotely to assess extinction risk of three subterranean aquatic species that are being considered for listing under the U.S. Endangered Species Act. We provided experts an empirical threat assessment for each known locality over a video conference and recorded judgments on the probability of population persistence over four generations with online submission forms and R‐shiny apps available through the SHELF package. Despite large uncertainty for all populations, there were key differences between species’ risk of extirpation based on spatial variation in dominant threats, local land use and management practices, and species’ microhabitat. The resulting probability distributions provided decision makers with a full picture of uncertainty that was consistent with the probabilistic nature of risk assessments. Discussion among experts during SHELF's behavioral aggregation stage clearly documented dominant threats (e.g., development, timber harvest, animal agriculture, and cave visitation) and their interactions with local cave geology and species’ habitat. Our virtual implementation of the SHELF protocol demonstrated the flexibility of the approach for conservation applications operating on budgets and time lines that can limit in‐person meetings of geographically dispersed experts.

Imitating evolution’s tinkering by protein engineering reveals extension of human galectin-7 activity - Anna-Kristin Ludwig; Malwina Michalak; Adele Gabba; Tanja J. Kutzner; Donella M. Beckwith; Forrest G. FitzGerald; Gabriel García Caballero; Joachim C. Manning; Mark Kriegsmann; Herbert Kaltner; Paul V. Murphy; Maré Cudic; et al. (Histochemistry and Cell Biology, 2021)
Wild-type lectins have distinct types of modular design. As a step to explain the physiological importance of their special status, hypothesis-driven protein engineering is used to generate variants. Concerning adhesion/growth-regulatory galectins, non-covalently associated homodimers are commonly encountered in vertebrates. The homodimeric galectin-7 (Gal-7) is a multifunctional context-dependent modulator. Since the possibility of conversion from the homodimer to hybrids with other galectin domains, i.e. from Gal-1 and Gal-3, has recently been discovered, we designed Gal-7-based constructs, i.e. stable (covalently linked) homo- and heterodimers. They were produced and purified by affinity chromatography, and the sugar-binding activity of each lectin unit proven by calorimetry. Inspection of profiles of binding of labeled galectins to an array-like platform with various cell types, i.e. sections of murine epididymis and jejunum, and impact on neuroblastoma cell proliferation revealed no major difference between natural and artificial (stable) homodimers. When analyzing heterodimers, acquisition of altered properties was seen. Remarkably, binding properties and activity as effector can depend on the order of arrangement of lectin domains (from N- to C-termini) and on the linker length. After dissociation of the homodimer, the Gal-7 domain can build new functionally active hybrids with other partners. This study provides a clear direction for research on defining the full range of Gal-7 functionality and offers the perspective of testing applications for engineered heterodimers.

Cannabidiol reduces withdrawal symptoms in nicotine-dependent rats - Lauren C. Smith; Lani Tieu; Raymond T. Suhandynata; Brent Boomhower; Melissa Hoffman; Yadira Sepulveda; Lieselot L. G. Carrette; Jeremiah D. Momper; Robert L. Fitzgerald; Kate Hanham; Joseph Dowling; Marsida Kallupi; et al. (Psychopharmacology, 2021)

Associations between Antiretrovirals and Cognitive Function in Women with HIV - Leah H. Rubin; Yuliang Li; Kathryn C. Fitzgerald; Raha Dastgheyb; Amanda B. Spence; Pauline M. Maki; Anjali Sharma; Deborah R. Gustafson; Joel Milam; Kathleen M. Weber; Adaora A. Adimora; Norman J. Haughey; et al. (Journal of Neuroimmune Pharmacology, 2021)

Associations between Antiretroviral Drugs on Depressive Symptomatology in Homogenous Subgroups of Women with HIV - Dionna W. Williams; Yuliang Li; Raha Dastgheyb; Kathryn C. Fitzgerald; Pauline M. Maki; Amanda B. Spence; Deborah R. Gustafson; Joel Milam; Anjali Sharma; Adaora A. Adimora; Igho Ofotokun; Margaret A. Fischl; et al. (Journal of Neuroimmune Pharmacology, 2021)

Evaluating a herpetofaunal monitoring program in the Rolling Plains of Texas - James S. Cash; Donald C. Ruthven; Lee A. Fitzgerald (Environmental Monitoring and Assessment, 2021)

Correction to: Silicic conduits as supersized tuffisites: Clastogenic influences on shifting eruption styles at Cordón Caulle volcano (Chile) - C. Ian Schipper; Jonathan M. Castro; Ben M. Kennedy; Hugh Tuffen; Jack Whattam; Fabian B. Wadsworth; Rebecca Paisley; Rebecca H. Fitzgerald; Emma Rhodes; Lauren N. Schaefer; Paul A. Ashwell; Pablo Forte; et al. (Bulletin of Volcanology, 2021)

Silicic conduits as supersized tuffisites: Clastogenic influences on shifting eruption styles at Cordón Caulle volcano (Chile) - C. Ian Schipper; Jonathan M. Castro; Ben M. Kennedy; Hugh Tuffen; Jack Whattam; Fabian B. Wadsworth; Rebecca Paisley; Rebecca H. Fitzgerald; Emma Rhodes; Lauren N. Schaefer; Paul A. Ashwell; Pablo Forte; et al. (Bulletin of Volcanology, 2021)

TF-containing MUC1 glycopeptides fail to entice Galectin-1 recognition of tumor-associated Thomsen-Freidenreich (TF) antigen (CD176) in solution - Forrest G. FitzGerald; Maria C. Rodriguez Benavente; Camelia Garcia; Yaima Rivero; YashoNandini Singh; Hongjie Wang; Gregg B. Fields; Maré Cudic (Glycoconjugate Journal, 2020)

Porcine reproductive and respiratory syndrome virus: phylogenetic analysis of circulating strains in the Republic of Ireland from 2016 to 2017 - Rose M. Fitzgerald; Patrick J. Collins; Michael J. McMenamey; Finola C. Leonard; Hugh McGlynn; Helen O’Shea (Archives of Virology, 2020)

The spatial ecology of brown trout (Salmo trutta) and dace (Leuciscus leuciscus) in an artificially impounded riverine habitat: results from an acoustic telemetry study - J. Barry; P. McLoone; C. J. Fitzgerald; J. J. King (Aquatic Sciences, 2020)

A global dataset and model of earthquake-induced landslide fatalities - M. Anna Nowicki Jessee; M. W. Hamburger; M. R. Ferrara; A. McLean; C. FitzGerald (Landslides, 2020)

Coral reef annihilation, persistence and recovery at Earth’s youngest volcanic island - P. F. Smallhorn-West; J. B. Garvin; D. A. Slayback; T. M. DeCarlo; S. E. Gordon; S. H. Fitzgerald; T. Halafihi; G. P. Jones; T. C. L. Bridge (Coral Reefs, 2020)

Environmental impact assessment of uranium exploration and development on indigenous land in Labrador (Canada): a community-driven initiative - Atanu Sarkar; Derek H. C. Wilton; Erica Fitzgerald; Abhishek Sharma; Abhinav Sharma; Akshay Jinka Sathya (Environmental Geochemistry and Health, 2019)

Trophic niche segregation among herbivorous serrasalmids from rapids of the lower Xingu River, Brazilian Amazon - Marcelo C. Andrade; Daniel B. Fitzgerald; Kirk O. Winemiller; Priscilla S. Barbosa; Tommaso Giarrizzo (Hydrobiologia, 2019)

Migratory birds as vehicles for parasite dispersal? Infection by avian haemosporidians over the year and throughout the range of a long‐distance migrant - Paulo C. Pulgarín‐R; Camila Gómez; Nicholas J. Bayly; Staffan Bensch; Alyssa M. FitzGerald; Naima Starkloff; Jeremy J. Kirchman; Ana M. González‐Prieto; Keith A. Hobson; Judit Ungvari‐Martin; Heather Skeen; María Isabel Castaño; et al. (Journal of Biogeography, 2019)
Aim The role of migratory birds in the spread of parasites is poorly known, in part because migratory strategies and behaviours potentially affecting transmission are not easy to study. We investigated the dynamics of infection by blood parasites through the annual cycle of a long‐distance Nearctic–Neotropical migratory songbird to examine the role of this species in dispersing parasites between continents. Location The Americas. Taxon Grey‐cheeked Thrush ( Catharus minimus , Aves, Passeriformes, Turdidae), Birds. Methods We used molecular and microscopy screening of haemosporidian parasites ( Plasmodium , Haemoproteus , and Leucocytozoon ) to examine the prevalence, distribution, and diversity of lineages through the annual cycle (breeding, migration, and wintering) of the grey‐cheeked thrush in North and Central America, Santa Marta mountains, the Andes, and the Amazon. We aimed to identify transmission areas, to examine the degree of sharing of haemosporidian lineages with resident birds in various areas and to assess the potential role of immunologically naïve juvenile individuals in parasite transmission. Results Prevalence and lineage diversity of haemosporidians varied significantly over time, being higher during breeding and fall and spring migration, and declining during wintering. Grey‐cheeked thrush shared few parasite lineages with tropical resident birds and slightly more lineages with other migratory and resident boreal species. We detected gametocytes in blood during spring migration stopover, but these were of lineages not found in resident tropical birds, indicating relapses of parasites transmitted elsewhere. Transmission likely occurs mostly on the breeding grounds, where juveniles and adults carried lineages restricted to closely related species of thrushes and other species of boreal birds. Main conclusions Long‐distance migratory songbirds are likely not important dispersers of blood parasites because there are ecological and evolutionary barriers to the interchange of parasites across vastly separated areas. Further work with thorough spatial and temporal sampling across other species, and considering the role of vectors, is necessary to understand the ecological and evolutionary factors explaining the distribution of parasites over broad scales.

Climate change impact and adaptation for wheat protein - Senthold Asseng; Pierre Martre; Andrea Maiorano; Reimund P. Rötter; Garry J. O’Leary; Glenn J. Fitzgerald; Christine Girousse; Rosella Motzo; Francesco Giunta; M. Ali Babar; Matthew P. Reynolds; Ahmed M. S. Kheir; et al. (Global Change Biology, 2019)
Wheat grain protein concentration is an important determinant of wheat quality for human nutrition that is often overlooked in efforts to improve crop production. We tested and applied a 32‐multi‐model ensemble to simulate global wheat yield and quality in a changing climate. Potential benefits of elevated atmospheric CO 2 concentration by 2050 on global wheat grain and protein yield are likely to be negated by impacts from rising temperature and changes in rainfall, but with considerable disparities between regions. Grain and protein yields are expected to be lower and more variable in most low‐rainfall regions, with nitrogen availability limiting growth stimulus from elevated CO 2 . Introducing genotypes adapted to warmer temperatures (and also considering changes in CO 2 and rainfall) could boost global wheat yield by 7% and protein yield by 2%, but grain protein concentration would be reduced by −1.1 percentage points, representing a relative change of −8.6%. Climate change adaptations that benefit grain yield are not always positive for grain quality, putting additional pressure on global wheat production.

Multimodel ensembles improve predictions of crop–environment–management interactions - Daniel Wallach; Pierre Martre; Bing Liu; Senthold Asseng; Frank Ewert; Peter J. Thorburn; Martin van Ittersum; Pramod K. Aggarwal; Mukhtar Ahmed; Bruno Basso; Christian Biernath; Davide Cammarano; et al. (Global Change Biology, 2018)
A recent innovation in assessment of climate change impact on agricultural production has been to use crop multimodel ensembles ( MME s). These studies usually find large variability between individual models but that the ensemble mean (e‐mean) and median (e‐median) often seem to predict quite well. However, few studies have specifically been concerned with the predictive quality of those ensemble predictors. We ask what is the predictive quality of e‐mean and e‐median, and how does that depend on the ensemble characteristics. Our empirical results are based on five MME studies applied to wheat, using different data sets but the same 25 crop models. We show that the ensemble predictors have quite high skill and are better than most and sometimes all individual models for most groups of environments and most response variables. Mean squared error of e‐mean decreases monotonically with the size of the ensemble if models are added at random, but has a minimum at usually 2–6 models if best‐fit models are added first. Our theoretical results describe the ensemble using four parameters: average bias, model effect variance, environment effect variance, and interaction variance. We show analytically that mean squared error of prediction ( MSEP ) of e‐mean will always be smaller than MSEP averaged over models and will be less than MSEP of the best model if squared bias is less than the interaction variance. If models are added to the ensemble at random, MSEP of e‐mean will decrease as the inverse of ensemble size, with a minimum equal to squared bias plus interaction variance. This minimum value is not necessarily small, and so it is important to evaluate the predictive quality of e‐mean for each target population of environments. These results provide new information on the advantages of ensemble predictors, but also show their limitations.

Influence of Green Seaweed ( Ulva rigida ) Supplementation on the Quality and Shelf Life of Atlantic Salmon Fillets - Natasha C. Moroney; Alex H. L. Wan; Anna Soler-Vila; Michael N. O’Grady; Richard D. FitzGerald; Mark P. Johnson; Joseph P. Kerry (Journal of Aquatic Food Product Technology, 2017)

High-risk individuals’ perceptions of reproductive genetic testing for CDH1 mutations - Nina Hallowell; Shirlene Badger; Sue Richardson; Carlos Caldas; Richard H. Hardwick; Rebecca C. Fitzgerald; Julia Lawton (Familial Cancer, 2017)

Adaptation to copper stress influences biofilm formation in Alteromonas macleodii - Kathleen D. Cusick; Jason R. Dale; Lisa A. Fitzgerald; Brenda J. Little; Justin C. Biffinger (Biofouling, 2017)

The Cognitive Role of the Globus Pallidus interna; Insights from Disease States - M. J. Gillies; J. A. Hyam; A. R. Weiss; C. A. Antoniades; R. Bogacz; J. J. Fitzgerald; T. Z. Aziz; M. A. Whittington; Alexander L. Green (Experimental Brain Research, 2017)

Reduced pro-inflammatory responses to Staphylococcus aureus bloodstream infection and low prevalence of enterotoxin genes in isolates from patients on haemodialysis - S. McNicholas; A. Fe Talento; J. O’Gorman; M. M. Hannan; M. Lynch; C. M. Greene; P. J. Conlon; A. C. Shore; D. C. Coleman; H. Humphreys; D. Fitzgerald-Hughes (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Fine mapping and candidate gene analysis of two loci conferring resistance to Phytophthora sojae in soybean - Linghong Li; Feng Lin; Weidong Wang; Jieqing Ping; Joshua C. Fitzgerald; Meixia Zhao; Shuai Li; Lianjun Sun; Chunmei Cai; Jianxin Ma (Theoretical and Applied Genetics, 2016)

Connexin Hemichannels: Methods for Dye Uptake and Leakage - Ross G. Johnson; Hung C. Le; Kristen Evenson; Shelby W. Loberg; Tori M. Myslajek; Andrea Prabhu; Ann-Marie Manley; Colette O’Shea; Haiying Grunenwald; Madelaine Haddican; Patrick M. Fitzgerald; Timothy Robinson; et al. (The Journal of Membrane Biology, 2016)

Angiotensin Converting Enzyme and Dipeptidyl Peptidase-IV Inhibitory, and Antioxidant Activities of a Blue Mussel ( Mytilus edulis ) Meat Protein Extract and Its Hydrolysates - Adriana C. Neves; Pádraigín A. Harnedy; Richard J. FitzGerald (Journal of Aquatic Food Product Technology, 2016)

Chemical contamination of soils in the New York City area following Hurricane Sandy - Amy C. Mandigo; Dana J. DiScenza; Alison R. Keimowitz; Neil Fitzgerald (Environmental Geochemistry and Health, 2016)

An investigation of the factors effecting high-risk individuals’ decision-making about prophylactic total gastrectomy and surveillance for hereditary diffuse gastric cancer (HDGC) - Nina Hallowell; Shirlene Badger; Sue Richardson; Carlos Caldas; Richard H. Hardwick; Rebecca C. Fitzgerald; Julia Lawton (Familial Cancer, 2016)

Genome-wide association of familial prostate cancer cases identifies evidence for a rare segregating haplotype at 8q24.21 - Craig C. Teerlink; Daniel Leongamornlert; Tokhir Dadaev; Alun Thomas; James Farnham; Robert A. Stephenson; Shaun Riska; Shannon K. McDonnell; Daniel J. Schaid; William J. Catalona; S. Lilly Zheng; Kathleen A. Cooney; et al. (Human Genetics, 2016)

Identification and molecular mapping of Rps11, a novel gene conferring resistance to Phytophthora sojae in soybean - Jieqing Ping; Joshua C. Fitzgerald; Chunbao Zhang; Feng Lin; Yonghe Bai; Dechun Wang; Rajat Aggarwal; Maqsood Rehman; Oswald Crasta; Jianxin Ma (Theoretical and Applied Genetics, 2016)

Proceedings of the second international molecular pathological epidemiology (MPE) meeting - Shuji Ogino; Peter T. Campbell; Reiko Nishihara; Amanda I. Phipps; Andrew H. Beck; Mark E. Sherman; Andrew T. Chan; Melissa A. Troester; Adam J. Bass; Kathryn C. Fitzgerald; Rafael A. Irizarry; Karl T. Kelsey; et al. (Cancer Causes & Control, 2015)

Acute effect of high-intensity cycling exercise on carotid artery hemodynamic pulsatility - Matthew C. Babcock; Wesley K. Lefferts; William E. Hughes; Kimberly L. Fitzgerald; Briana K. Leyer; Jessica G. Redmond; Kevin S. Heffernan (European Journal of Applied Physiology, 2015)

The RIG-I-like helicase receptor MDA5 (IFIH1) is involved in the host defense against Candida infections - M. Jaeger; R. van der Lee; S.-C. Cheng; M. D. Johnson; V. Kumar; A. Ng; T. S. Plantinga; S. P. Smeekens; M. Oosting; X. Wang; W. Barchet; K. Fitzgerald; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Effects of oxycodone on brain responses to emotional images - Margaret C. Wardle; Daniel A. Fitzgerald; Michael Angstadt; Christine A. Rabinak; Harriet de Wit; K. Luan Phan (Psychopharmacology, 2014)

The behavioral pharmacology of zolpidem: evidence for the functional significance of α1-containing GABAA receptors - Amanda C. Fitzgerald; Brittany T. Wright; Scott A. Heldt (Psychopharmacology, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Alcohol attenuates amygdala–frontal connectivity during processing social signals in heavy social drinkers - Stephanie M. Gorka; Daniel A. Fitzgerald; Andrea C. King; K. Luan Phan (Psychopharmacology, 2013)

Epidemiology of invasive pneumococcal disease and vaccine provision in a tertiary referral center - C. Rock; C. Sadlier; J. Fitzgerald; M. Kelleher; C. Dowling; S. Kelly; C. Bergin (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Esperanto for histones: CENP-A, not CenH3, is the centromeric histone H3 variant - W. C. Earnshaw; R. C. Allshire; B. E. Black; K. Bloom; B. R. Brinkley; W. Brown; I. M. Cheeseman; K. H. A. Choo; G. P. Copenhaver; J. G. DeLuca; A. Desai; S. Diekmann; et al. (Chromosome Research, 2013)

Transmission of endemic ST22-MRSA-IV on four acute hospital wards investigated using a combination of spa, dru and pulsed-field gel electrophoresis typing - E. Creamer; A. C. Shore; A. S. Rossney; A. Dolan; O. Sherlock; D. Fitzgerald-Hughes; D. J. Sullivan; P. M. Kinnevey; P. O’Lorcain; R. Cunney; D. C. Coleman; H. Humphreys (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Embryonic development in ballan wrasse Labrus bergylta - J. D’Arcy; E. Dunaevskaya; J. W. Treasurer; O. Ottesen; J. Maguire; N. Zhuravleva; A. Karlsen; C. Rebours; R. D. FitzGerald (Journal of Fish Biology, 2012)
Eight primary embryonic developmental stages were assigned to eggs of ballan wrasse Labrus bergylta using key morphological features following standardized nomenclature: Ia, Ib, II, III, IV, V, VI and VI+, reared from single family clutches under comparable environmental conditions in Ireland and Norway. Development in L. bergylta is typical of demersal marine finfish species with a short egg stage. Hatching occurred c . 123 h post‐fertilization (hpf) equivalent to 62·5 degree days at 12·2 ± 1·10° C (mean ± s.d. ), after which the larvae swam intermittently near the surface of the water column.

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Priority Actions for Sustainable Forest Management in the International Year of Forests - DOMINICK A. DELLASALA; JOHN M. FITZGERALD; BENGT‐GUNNAR JONSSON; JEFFREY A. MCNEELY; BENJAMIN DELALI DOVIE; MARTIN DIETERICH; PATRICIA MAJLUF; SIMON C. NEMTZOV; OWEN T. NEVIN; E. CHRISTIEN M. PARSONS; JAMES E.M. WATSON (Conservation Biology, 2012)

Pre-logging carbon accounts in old-growth forests, via allometry: An example of mixed-forest in Tasmania, Australia - C. Dean; N. B. Fitzgerald; G. W. Wardell-Johnson (Plant Biosystems, 2012)

Resilience to fire of Dracophyllum subulatum (Ericaceae) frost flat heathland, a rare ecosystem in central North Island, New Zealand - M C Smale; N B Fitzgerald; S J Richardson (New Zealand Journal of Botany, 2011)
We measured secondary succession in permanent plots for 15 years after a lightning‐induced fire in a 90‐year‐old frost flat heathland dominated by Dracophyllum subulatum at Rangitaiki, North Island, New Zealand. We placed this succession in the longer term context provided by earlier published data from the same site. Species re‐establishment was rapid, with all of the consistently present species of mature heathland present by 15 years. The new Dracophyllum population has reached its pre‐burn density, although cover is still minimal. Vascular plant cover began to decline 11 years after fire, but non‐vascular cover continued to increase. Poa cita declined dramatically in abundance after 11 years. Earlier studies at the site demonstrate that nearly the entire species complement of mature heathland is present by 25 years, indication of a direct succession. With substantial resilience to fire, frost flat heathland is a fire‐adapted ecosystem in a country where such ecosystems are rare.

Barrett’s oesophagus: an ideal model to study cancer genetics - Massimiliano di Pietro; Rebecca C. Fitzgerald (Human Genetics, 2009)

Increased protein carbonylation in leaves of Arabidopsis and soybean in response to elevated [CO2] - Quan-Sheng Qiu; Joan L. Huber; Fitzgerald L. Booker; Vanita Jain; Andrew D. B. Leakey; Edwin L. Fiscus; Peter M. Yau; Donald R. Ort; Steven C. Huber (Photosynthesis Research, 2008)

Ga3+ as a mechanistic probe in Fe3+ transport: characterization of Ga3+ interaction with FbpA - Katherine D. Weaver; Jared J. Heymann; Arnav Mehta; Petra L. Roulhac; Damon S. Anderson; Andrew J. Nowalk; Pratima Adhikari; Timothy A. Mietzner; Michael C. Fitzgerald; Alvin L. Crumbliss (JBIC Journal of Biological Inorganic Chemistry, 2008)

Atorvastatin Therapy is Associated with Greater and Faster Cerebral Hemodynamic Response - Guofan Xu; Michele E. Fitzgerald; Zhifei Wen; Sean B. Fain; David C. Alsop; Timothy Carroll; Michele L. Ries; Howard A. Rowley; Mark A. Sager; Sanjay Asthana; Sterling C. Johnson; Cynthia M. Carlsson (Brain Imaging and Behavior, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Describing the structure and assembly of protein filaments by EPR spectroscopy of spin-labeled side chains - Madhu S. Budamagunta; John F. Hess; Paul G. Fitzgerald; John C. Voss (Cell Biochemistry and Biophysics, 2007)

The phenotypic expression of three MSH2 mutations in large Newfoundland families with Lynch syndrome - Susan Stuckless; Patrick S. Parfrey; Michael O. Woods; Janet Cox; G. William Fitzgerald; Jane S. Green; Roger C. Green (Familial Cancer, 2007)

Alteration of Ecosystem Function by Zebra Mussels in Oneida Lake: Impacts on Submerged Macrophytes - B. Zhu; D. G. Fitzgerald; C. M. Mayer; L. G. Rudstam; E. L. Mills (Ecosystems, 2006)

Heavy Metal Accumulation in Four Species of Sea Turtles from the Baja California Peninsula, Mexico - Susan C. Gardner; Sionnan L. Fitzgerald; Baudilio Acosta Vargas; Lia Méndez Rodríguez (BioMetals, 2006)

Effect of caffeine ingestion on lymphocyte counts and subset activation in vivo following strenuous cycling - Nicolette C. Bishop; Christina Fitzgerald; Penny J. Porter; Gabriella A. Scanlon; Alice C. Smith (European Journal of Applied Physiology, 2005)

Metals in Horseshoe Crabs from Delaware Bay - J. Burger; C. Dixon; T. Shukla; N. Tsipoura; H. Jensen; M. Fitzgerald; R. Ramos; M. Gochfeld (Archives of Environmental Contamination and Toxicology, 2003)

Engineering Pathogen Resistance in Crop Plants - Matthew A. Campbell; Heather A. Fitzgerald; Pamela C. Ronald (Transgenic Research, 2002)

Daily dataset of 20th‐century surface air temperature and precipitation series for the European Climate Assessment - A. M. G. Klein Tank; J. B. Wijngaard; G. P. Können; R. Böhm; G. Demarée; A. Gocheva; M. Mileta; S. Pashiardis; L. Hejkrlik; C. Kern‐Hansen; R. Heino; P. Bessemoulin; et al. (International Journal of Climatology, 2002)
We present a dataset of daily resolution climatic time series that has been compiled for the European Climate Assessment (ECA). As of December 2001, this ECA dataset comprises 199 series of minimum, maximum and/or daily mean temperature and 195 series of daily precipitation amount observed at meteorological stations in Europe and the Middle East. Almost all series cover the standard normal period 1961–90, and about 50% extends back to at least 1925. Part of the dataset (90%) is made available for climate research on CDROM and through the Internet (at http://www.knmi.nl/samenw/eca ). A comparison of the ECA dataset with existing gridded datasets, having monthly resolution, shows that correlation coefficients between ECA stations and nearest land grid boxes between 1946 and 1999 are higher than 0.8 for 93% of the temperature series and for 51% of the precipitation series. The overall trends in the ECA dataset are of comparable magnitude to those in the gridded datasets. The potential of the ECA dataset for climate studies is demonstrated in two examples. In the first example, it is shown that the winter (October–March) warming in Europe in the 1976–99 period is accompanied by a positive trend in the number of warm‐spell days at most stations, but not by a negative trend in the number of cold‐spell days. Instead, the number of cold‐spell days increases over Europe. In the second example, it is shown for winter precipitation between 1946 and 1999 that positive trends in the mean amount per wet day prevail in areas that are getting drier and wetter. Because of its daily resolution, the ECA dataset enables a variety of empirical climate studies, including detailed analyses of changes in the occurrence of extremes in relation to changes in mean temperature and total precipitation. Copyright © 2002 Royal Meteorological Society.

Supercooling capacity of Eurasian and North American populations of parasitoids of the Russian wheat aphid, >Diuraphis noxia - Robert M. Nowierski; Bryan C. Fitzgerald (BioControl, 2002)

An Examination of the Atmospheric Chemistry of Mercury Using 210Pb and 7Be - Carl H. Lamborg; William F. Fitzgerald; William C. Graustein; Karl K. Turekian (Journal of Atmospheric Chemistry, 2000)

Probiotics: from myth to reality. Demonstration of functionality in animal models of disease and in human clinical trials - Colum Dunne; Lisa Murphy; Sarah Flynn; Liam O'Mahony; Sile O'Halloran; Maria Feeney; Darrin Morrissey; Gerardine Thornton; Gerald Fitzgerald; Charles Daly; Barry Kiely; Eamonn M. M. Quigley; et al. (Antonie van Leeuwenhoek, 1999)

The use of image analysis to study developmental variation in micropropagated potato (Solanum tuberosum L.) plants - A. C. Cassells; B. Kowalski; D. M. Fitzgerald; G. A. Murphy (Potato Research, 1999)

Human endothelial cells cultured on microporous filters used for leukocyte transmigration studies form monolayers on both sides of the filter - A. Jill Mackarel; David C. Cottell; Muiris X. Fitzgerald; Clare M. O’Connor (In Vitro Cellular & Developmental Biology - Animal, 1999)

Annual and seasonal patterns of litter‐fall of hard beech (Nothofagus truncata) and silver beech (Nothofagus menziesil) in relation to reproduction - J. C. Alley; B. M. Fitzgerald; P. H. Berben; S. J. Haslett (New Zealand Journal of Botany, 1998)
Vegetative and reproductive components of litter‐fall of hard beech were measured for five years and of silver beech for four years under mature trees in the Orongorongo Valley, near Wellington, New Zealand. Mean annual total litter‐fall of hard beech (477 g m ‐2 ) included 318 g of leaves and 109 g of twigs; that of silver beech (463 g m ‐2 ) included 295 g of leaves and 164 g of twigs. In one year only (1994/95) both species flowered and seeded prolifically. The two species produced similar numbers of seeds (hard beech 4866 seeds m ‐2 ; silver beech 5551 seeds m ‐2 ) but litter from male flowers, seeds, and cupules of hard beech weighed 232 g m ‐2 compared with only 59 g m‐ 2 for silver beech. Seasonal patterns of leaf‐fall of the two species also differed substantially; peak leaf‐fall of hard beech was in November and of silver beech in April/ May. These differences in the amounts and timing of the components of litter‐fall between species and years will have important ecosystem effects.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)